2015
DOI: 10.1111/vec.12304
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure in dogs and cats

Abstract: The prognosis for ALF depends upon the etiology, the degree of liver damage, and the response to therapy. In veterinary medicine, the prognosis is generally poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 182 publications
(304 reference statements)
3
56
0
Order By: Relevance
“…Coagulation testing is an important component of diagnostic evaluation in dogs and cats. Coagulation studies are recommended for small animal patients with evidence of abnormal bleeding, trauma, or liver disease; to monitor for disseminated intravascular coagulation; and for presurgical screening in selected cases, with recent reviews providing recommendations for comprehensive diagnostic evaluation when coagulopathy is suspected . A large retrospective study of dogs and cats undergoing ultrasound‐guided biopsies found that prolongation of activated partial thromboplastin time (aPTT) was a risk factor for bleeding complications in cats, and prolongation of prothrombin time (PT) was a risk factor in dogs, though the numbers of animals experiencing complications even among those with prolonged times was relatively small .…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation testing is an important component of diagnostic evaluation in dogs and cats. Coagulation studies are recommended for small animal patients with evidence of abnormal bleeding, trauma, or liver disease; to monitor for disseminated intravascular coagulation; and for presurgical screening in selected cases, with recent reviews providing recommendations for comprehensive diagnostic evaluation when coagulopathy is suspected . A large retrospective study of dogs and cats undergoing ultrasound‐guided biopsies found that prolongation of activated partial thromboplastin time (aPTT) was a risk factor for bleeding complications in cats, and prolongation of prothrombin time (PT) was a risk factor in dogs, though the numbers of animals experiencing complications even among those with prolonged times was relatively small .…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of dogs with CH, the etiology remains undetermined and is considered to be of idiopathic origin . AH can be induced by a variety of stimuli, including toxins, adverse drug reactions, infectious disease ( i.e, canine adenovirus‐1 infection, leptospirosis), or is considered idiopathic . In the last few decades, copper toxicosis is recognized with increased frequency as an etiologic factor in the development of both AH and CH in several dog breeds, including the Labrador retriever …”
mentioning
confidence: 99%
“…4 AH can be induced by a variety of stimuli, including toxins, adverse drug reactions, infectious disease (i.e, canine adenovirus-1 infection, leptospirosis), or is considered idiopathic. 1,2,[5][6][7] In the last few decades, copper toxicosis is recognized with increased frequency as an etiologic factor in the development of both AH and CH in several dog breeds, [8][9][10][11][12] including the Labrador retriever. [13][14][15][16] Clinical signs of liver disease are usually not very specific, except in end-stage liver disease, where icteric mucous membranes and presence of ascites might indicate advanced liver disease.…”
mentioning
confidence: 99%
“…In human medicine, acute liver failure (ALF) has been defined as progression of acute liver injury, resulting in the development of hepatic encephalopathy (HE) within 8 weeks of the onset of hyperbilirubinemia and the presence of coagulopathy, in the absence of previous hepatic disease …”
Section: Introductionmentioning
confidence: 99%
“…Where possible, initial treatment consists of correction of the underlying cause and administration of an antidote, if available . However, the cornerstone of therapy remains supportive care, including IV fluids, correction of electrolyte abnormalities, hepatic cytoprotective agents (eg, silymarin, vitamin E, S‐adenosyl‐L‐methionine [SAMe], and N‐acetylcysteine [NAC]), nutritional management to allow recovery of the liver and reduce the signs of encephalopathy, and management of secondary complications (eg, coagulopathies, hypoglycemia, HE, and infection) …”
Section: Introductionmentioning
confidence: 99%